Discrete twin evolution in Mg alloys using a novel crystal plasticity finite element model. (1st May 2018) - Cheng, Jiahao; Shen, Jinlei; Mishra, Raj K.; Ghosh, Somnath
Abstract: This paper implements the image-based crystal plasticity FE model with explicit twin evolution, developed in [1, 2], to study mechanisms of deformation and twinning in polycrystalline microstructures of the Mg alloy AZ31. The physics of twin nucleation, propagation and interaction with slip systems are represented in the constitutive formulation and implemented in a FE code. Image-based simulations are conducted for statistically equivalent representative volume elements, for which the morphological and crystallographic parameters are statistically equivalent to those observed in EBSD data of experimental samples. Validation studies show satisfactory agreement of the stress-strain response with experiments. Analyses of deformation in AZ31 reveal various deformation mechanisms captured by the model. An important contribution of this paper is in the exploration of various twin-related local phenomenon and deformation mechanisms using tricrystalline and polycrystalline models. Several underlying mechanisms are revealed through these simulations. Graphical abstract: (a) Crystal plasticity FE simulation results showing explicit twins: (a) Contours of twin evolution with deformation (elements in red are twinned) and distribution of twin system resolved shear stress (TS-RSS) during twin propagation and thickening in a tricrystalline specimen, and (b) Stress-strain curves from experiments and simulation results for a polycrystalline model. Image 1